Preparation and Physical Properties Evaluation of glass/wood Pulp Fibers wet-laid Felts. Issue 16 (28th November 2022) - Hu, Jian; Han, Ruonan; Yang, Yong
ABSTRACT: Mechanical properties of pure glass fiber wet-laid felts with no adhesives are relatively poor and limit the using. The aim of this study is to analyze the hybrid effects of glass/wood pulp wet-laid felt (GWFF) via papermaking technology. The influence of wood pulp fiber weight ratios on the physical properties of GWFFs is studied. The results show that GWFFs can obtain excellent uniformity when wood pulp fiber weight ratios are less than 50%. GWFFs with 20% wood pulp fiber weight ratios exhibit optimum break elongation, flexural property, and bursting strength. It also finds that tensile strength and Young's modulus increase with wood pulp fiber weight ratios due to the effect of surface roughness of fibers and hydrogen bonds between fibers.